Influence of host plant species and flush growth stage on the Asian citrus psyllid, Diaphorina citri Kuwayama - Leong, Stephen Chan Teck; Abang, Fatimah; Beattie, Andrew; Kueh, Roland Jui Heng; Wong, Sing King (Science Publications, 2011)
Problem statement: In order to establish the important host range of D. citri, the performance of this psyllid on different rutacous host plants was assessed. Apparent regional differences in host preferences of D. citri as noted above and the need for empirical knowledge of its host preferences in Malaysia where it is lacking. Approach: Experiments on host plant preference between citrus, jasmine orange and curry leaf were conducted over a period of 14 days in the field cage in October 1998 at the agricultural research centre, Semonggok, 15 km from Kuching, Kuching Division, Sarawak in Malaysia. Results: A comparative life cycle study of the Asian Citrus Psyllid Diaphorina citri Kuwayama on three different Rutaceous plant hosts namely citrus, jasmine orange and curry leaf plants was conducted inside the temperature controlled growth chamber maintain at 26 ± 1°C temperature, 75-80% relative humidity with artificial illumination intensity of 10,000 lux equipped with a photoperiod of 14:10 h light: dark regime to permit normal growth. Conclusion: The screenhouse studies confirmed that D. citri can colonise and breed on citrus, jasmine orange and curry leaf plant and that jasmine orange is the preferred host. It is also confirmed that females prefer to oviposit on immature flush 3-10 mm in length. In growth chamber experiments the life cycle of the psyllid was 18.5 days on jasmine orange, 19.0 days on citrus and 23.0 days on curry leaf.